2019
DOI: 10.1021/acscatal.9b00249
|View full text |Cite
|
Sign up to set email alerts
|

Silver Effect in Regiodivergent Gold-Catalyzed Hydroaminations

Abstract: We report a silver-induced switching of regioselectivity in gold-catalyzed reactions, and we provide mechanistic evidence to suggest a true “silver effect”: that is, one that is implicated in the catalytic process itself, via σ-gold π-silver acetylides. These results are of significance because they clearly show that the use of silver as halide abstractors in gold-catalyzed reactions may result in “silver effects” when terminal alkyne substrates are involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 65 publications
1
16
0
Order By: Relevance
“…1 H‐NMR showed that aminal 8 could unambiguously arise from a 5‐ exo‐ dig pathway. The favored 5‐ exo‐ dig pathway at lower temperature is consistent with the known gold‐catalyzed cyclization of terminal alkynes [52] and suggest the possible involvement of a σ,π‐digold acetylide complex in the mechanism [53–57] . Thus, two distinct pathways can be considered to explain the observed temperature dependent regioselectivity: 1 ) the monogold pathway involving the formation of a five‐ ( 6 ) or six‐ ( 5 ) membered ring spirocyclic vinyl‐ammonium‐gold(I) species or, 2 ) the digold pathway involving the formation of a spirocyclic vinyl‐ammonium‐digold(I) ( 7 ) species [58,59] …”
Section: Resultssupporting
confidence: 76%
“…1 H‐NMR showed that aminal 8 could unambiguously arise from a 5‐ exo‐ dig pathway. The favored 5‐ exo‐ dig pathway at lower temperature is consistent with the known gold‐catalyzed cyclization of terminal alkynes [52] and suggest the possible involvement of a σ,π‐digold acetylide complex in the mechanism [53–57] . Thus, two distinct pathways can be considered to explain the observed temperature dependent regioselectivity: 1 ) the monogold pathway involving the formation of a five‐ ( 6 ) or six‐ ( 5 ) membered ring spirocyclic vinyl‐ammonium‐gold(I) species or, 2 ) the digold pathway involving the formation of a spirocyclic vinyl‐ammonium‐digold(I) ( 7 ) species [58,59] …”
Section: Resultssupporting
confidence: 76%
“…[53][54][55][56] Compared with the advances in heterogeneous goldc atalysis, the field of homogeneous gold catalysis startedt og row only in the first decade of the 21st century.O ver the past two decades, homogeneousg old catalysis has emerged as an eminent synthetic methodology.T he progress in the syntheses and applications of Au catalysts, related reaction mechanisms, and the future prospects of traditional Au I -catalyzed reactions have been reviewed by the groups of Hashmi, [57][58][59][60][61][62] Fürstner, [63,64] To ste, [65] Echavarren, [66][67][68] and others. [92,93,102,[94][95][96][97][98][99][100][101] Some reactions are best catalyzed when multiple Au centers are available to activate the reactants and/or intermediates. Being ah eavy atom with a5 d 10 6s 1 electronic configuration, the relativistic effects strongly affect the dynamics of the valence electrons of Au.…”
Section: Introductionmentioning
confidence: 99%
“…Hashmi and others have reviewed the applications of Au in the total synthesis of natural products and complex target molecules . Recent studies have also focused on the cooperative catalysis of Au with other metal/nonmetal catalysts for accelerating selective organic transformations . Some reactions are best catalyzed when multiple Au centers are available to activate the reactants and/or intermediates .…”
Section: Introductionmentioning
confidence: 99%
“…Studieso ns everal catalytic systems revealed al ong-overlooked "silver effect" in gold catalysis that show as ignificant difference in the reactivity with and without silver.T he addition of different silver salts to promote the chloride abstractiono ft he well-known[ AuCl(JohnPhos)] complex, which is widely used as ac atalytic precursor in many organic transformations, has been reported to afford the corresponding chloride-bridged gold(I) complexes (Figure 1, I)t ogether with the desired [Au(JohnPhos)Solvate] + species. [4] More recent studies have supported the controversy in the so called "silver effects", [3,5] showing that silver can interact with key in- [a] Dr.R. Visbal termediates such as vinyl gold species, giving compounds such as those shown in Figure 1( II).…”
Section: Introductionmentioning
confidence: 99%